Longitudinal impact of parent-teacher relationship on middle school students’ academic achievements in China - Fu, Wangqian; Pan, Qianqian; Yuan, Ying; Chen, Guanyu (Frontiers in Psychology, 2022)
Objective: The study aims to discuss the longitudinal impact of the parent-teacher relationship on students' academic achievements in China. Method: Based on the China Education Panel Survey (CEPS), covering the data from 438 classes of 112 schools in 28 county-level administrative areas in China, we used the hierarchical linear model (HLM) to analyze the data. Results: We found that the parents' active communication with teachers, parents' participation in parent meetings, teachers' active contact, whether parents are afraid to communicate with teachers, and parents' willingness to participate in parent meetings with parents have significant relationships with students' academic achievements. At the class level, the extent of teachers' stress from parents' requests and teachers' perception of respect from parents also affected students' academic achievements significantly in the Chinese context. Conclusions: There was a longitudinal association between the parent-teacher relationship and students' academic achievements. The practical implication was discussed in the paper.